Carbon fiber from direct carbonization of PEDOT:PSS precursor fibers - Leah E. Noble; Ruben Sarabia-Riquelme; E. Ashley Morris; Gehan S. Rupasinghe; Alexandra F. Paterson; Matthew C. Weisenberger (Carbon Trends)
An important factor limiting widespread carbon fiber utilization is the immense energy required for its manufacture. Specifically, the pre-carbonization stabilization processing step required for polyacrylonitrile and pitch fiber precursors accounts for a large portion of the total processing time and embodied energy associated with carbon fiber production. However, stabilization can be omitted and a direct carbonization performed for certain precursors, which are typically within the class of aromatic polymers. In this work, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) is identified as a new precursor for direct carbonization. PEDOT:PSS direct carbonization yielded non-fused, small-diameter carbon fibers free of surface defects and voids visible by SEM, with an unoptimized carbon fiber yield of 30–40 wt.%. A maximum tensile strength of 1.5 GPa and elastic modulus of 220 GPa were achieved upon direct carbonization to 1000 °C and 2700 °C, respectively. A relatively high apparent tensile strain to failure of approximately 2 % was also observed at 1000 °C. The evolution of fiber tensile and electrical properties with direct carbonization temperature was studied, in addition to crystal and chemical structural changes via WAXS and Raman spectroscopy. Furthermore, the effect of precursor PEDOT concentration (relative to PSS) on resultant carbon fiber properties was evaluated. It was also shown that the inclusion of an oxidative stabilization step prior to carbonization did not improve carbon fiber properties, demonstrating the suitability of PEDOT:PSS for direct carbonization.